PENGARUH KEBIJAKAN HUTANG DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK PERIODE 2014-2023 - Saputri, Devi; Jamaluddin (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Debt Policy and Investment Decisions on Company Value at PT Indocement Tunggal Prakarsa Tbk for the period 2014-2023. The method used in this research is quantitative using descriptive methods. The population in this study were the financial statements of PT Indocement Tunggal Prakarsa Tbk for the period 2014-2023. While the sample used is the financial position report and annual report on PT Indocement Tunggal Prakarsa Tbk for the period 2014-2023. The data analysis method used is descriptive statistical test, classical assumption test, multiple linear regression analysis, t test hypothesis testing, f test, and correlation and determination coefficient test. The results showed that partially, the Debt Policy has a negative and significant effect on Firm Value, where the Debt Policy has a tcount> ttable of (3.500)> 2.466 with a significance value of 0.010 <0.05. And partially, the Investment Decision has no effect and no significance on Firm Value, where the Investment Decision has a tcount < ttable of 0.726 < 2.466 with a significance value of 0.491 > 0.05. And Debt Policy and Investment Decisions simultaneously have a significant effect on Company Value at PT Indocement Tunggal Prakarsa Tbk for the 2014-2023 Period, where Fhitung> Ftabel of 6.771> 4.07 and a significance value of 0.023 <0.05.